Water solubilization of paclitaxel using polypeptides for cancer therapy. Issue 1 (17th November 2021) - Kawasaki, Riku; Kawamura, Shogo; Hino, Shodai; Yamana, Keita; Ikeda, Atsushi
Abstract : A water solubilization technique using biocompatible polypeptides via a mechanochemical approach was developed for the issues in the pharmaceutical industry. Abstract : To address problems in drug discovery, we developed approaches to solubilize hydrophobic compounds using polypeptides including poly-l -lysine (PLL) via high-speed vibration milling. The current method can be used to prepare highly concentrated dispersions of the anticancer drug paclitaxel. Moreover, the complex of paclitaxel with PLL efficiently induced cancer cell death via apoptosis without harmful side effects on healthy cells. Finally, we demonstrated that actively growing cancer cell spheroid growth was efficiently suppressed after treatment.